FINANCIAL ACCOUNTING: AN EXPLORATORY DICHOTOMY BETWEEN MACROS AND ROBOTIC PROCESS AUTOMATION (RPA) - Olubunmi, Alao., Amos, Tomomewo., Abimbola Abosede Joshua., Ige, Oludele Emmanuel (International Journal of Research Science and Management, 2023)
The 4th industrial revolution has created a scenario where automation has become the order of the day. Given the dynamic nature of businesses and financial accounting today, this work looks into the aspect of automation in this field. Using Microsoft Excel and UiPath as case studies to show the differences between macros and Robotic Process Automation, this work was able to establish, through related text, the importance and viabilities of both technologies. Going further, this work looked at the major differences that set them apart but concluded that in some cases, both technologies working hand-in-hand is a better option.